Financial system sustainability assessment model creation - Jelena Stankevičienė; Marta Nikanorova (Trends Economics and Management, 2019)
Purpose of the article: The article is devoted to analyse the sustainability in the financial system. Sustainability in financial systems leads to the financial institution's positive economic performance during the financial crisis. The sustainable financial system must keep the country's economy healthy, effective, and profitable, and this is one of the tasks the answer to which still is looked for. Methodology/methods: The article includes the observation of financial system sustainability approach, the analysis of the financial system structure, architecture, and soundness. In addition, positive and negative impacts of sustainability on financial systems are discussed. The literature analysis, comparison methods, quantitative analysis, the multiple objective optimization MULTIMOORA method, and the graphical representation were used in the article. Based on the MULTIMOORA method and the indicators of sustainability, the model to measure sustainability is implemented. Scientific aim: The main goal of this article is to create and adopt a model of sustainability in the financial system measurement. Findings: The results show that sustainability in financial systems helps the financial institution to maintain positive economic performance even in the crisis time. Conclusions: Sustainability of the financial system is measured according to the sustainability approach; the interaction of economic, social and environmental aspects should be considered. The multiple objective optimization was used to obtain sustainability in the financial system and the MULTIMOORA method was selected for the analysis of the financial system sustainability. For the analysis, 10 countries were selected, which joined the European Union in 2004, in other words, named as "A10" countries. MULTIMOORA proved that the financial system is a complex system, with interrelations between objectives and alternatives that are taken into account at the same time and ,different values of the indicators, representing a particular group of indicators.
Keywords: C69; G20; G32; 650; sustainability; financial system; structure of the financial system; MULTIMOORA method; financial ratios; financial market